Analysis of Social Work Practice Research Trends in the Post-Covid-19 Pandemic Era: A Bibliometric Study - Oman Sukmana; Juli Astutik; Hutri Agustino; Erinda Dwimagistri Sukmana (ARRUS Journal of Social Sciences and Humanities, 2026)
The study aims to examine issues and focus research related to post-COVID-19 pandemic social work practices using bibliometric analysis. Data was collected from the Scopus database with the keywords "social work practice" OR "Social work service" AND "Post Covid-19". Article documents were tracked through the Scopus database by year range criteria between 2022 and July 2024, subject area social sciences and psychology, document type article, and language English, and then obtained a total of 139 articles. Further analysis was carried out of 139 scientific publications using VOSviewer software to identify topic trends, collaborations, and research developments. The results showed that the study of social work practice in the post-pandemic COVID-19 era can be grouped into two major theme nodes, namely the social work theme node and the COVID-19 theme node. The social work practice theme node consists of sub-themes: social care, advocacy, disability, rights, inclusion, social care, coronavirus, anxiety, resilience, academics, child welfare, service, infection, control measures, and child protection. The research also revealed the emergence of new themes such as the use of digital technology and the development of adaptive social work intervention models in the post-pandemic era. These findings can be a benchmark for academics, practitioners, and stakeholders in developing research agendas and social work practices relevant to the needs of the post-COVID-19 pandemic community. Future recommendations are considered necessary to conduct a study of social work practice that focuses on sub-sub-themes such as anxiety, resilience, child welfare, social services, and social work practices related to child protection.